EXPERIMENTAL STUDY OF THE RESULTS OF PROFESSIONAL TRAINING OF MASTER'S LEVEL EDUCATION ACQUIRES - Сидор, Галина; Безугла , Людмила; Домбровська, Наталія; Зелінська, Галина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
To date, the study of the effectiveness of training in the professional training of applicants for the second masters level is recognized as one of the most important, which is considered by the world economic community. The scientific elaboration of this issue becomes especially relevant in the context of finding ways to modernize and reform it. The aim is to investigate the effectiveness of the use of training in professional training for applicants for the second masters level. To achieve this goal, the article uses general and special research methods, in particular: general scientific and special research methods – to ensure the achievement of this goal; abstract-logical and dialectical methods of analysis – to substantiate theoretical positions and conclusions. The relevance of the material presented in the scientific article is due to the need to implement innovative approaches to the training of applicants for the second masters level. Empirical material was collected and generalized on the quality of the training method, the level of teachers and the wishes of second-level applicants to improve the training form of education at the Chortkiv Educational and Scientific Institute of Entrepreneurship and Business. The questionnaire revealed a set of measures for effective training in the professional training of applicants for the second masters level. The management of the institute is invited to test (test in practice) the methods developed and proposed by the authors of the article, for effective training in the professional training of applicants for the second masters level. Attention is focused on the effectiveness of the use of training learning technologies, which involve the establishment of constructive interaction in the educational process and aimed at forming a competent specialist (applicant of the second masters level), able to successfully solve professional problems. The conclusion is made on the expediency of using trainings in the professional training of applicants of the second masters level in order to form their readiness to interact in professional activities.